2004
DOI: 10.1109/tcsvt.2004.831964
|View full text |Cite
|
Sign up to set email alerts
|

Real-time error protection of embedded codes for packet erasure and fading channels

Abstract: Abstract-Reliable real-time transmission of packetized embedded multimedia data over noisy channels requires the design of fast error control algorithms. For packet erasure channels, efficient forward error correction is obtained by using systematic Reed-Solomon (RS) codes across packets. For fading channels, state-of-the-art performance is given by a product channel code where each column code is an RS code and each row code is a concatenation of an outer cyclic redundancy check code and an inner rate-compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…There have been several works proposed to reduce the computational complexity of MD-FEC. We adopt the fast local search method [39] with complexity as in this work. To decode the coded video packets generated by the MD-FEC framework, the RS decoder located at each client terminal needs to know the configuration of RS code used in each segment.…”
Section: Application Layer Fecmentioning
confidence: 99%
“…There have been several works proposed to reduce the computational complexity of MD-FEC. We adopt the fast local search method [39] with complexity as in this work. To decode the coded video packets generated by the MD-FEC framework, the RS decoder located at each client terminal needs to know the configuration of RS code used in each segment.…”
Section: Application Layer Fecmentioning
confidence: 99%
“…Although the framework of this paper may resemble the works of [13], [28], [29], [38], [42] from the standpoint of considering transmission over channels with bit errors and packet erasures, it has to be noted that those articles consider neither the effects of embedding multiple antennas within an optimization problem nor the effects of using feedback for image delivery. Thus, this paper attempts at analyzing and quantifying performance improvements of end-to-end image delivery systems over wireless tandem channels as the result of utilizing multiple antennas as well as multiple round feedback transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient algorithms for finding optimal rate-based solutions exist [19] and optimal distortionbased solutions can be found in certain scenarios. In the case of a packet erasure channel, distortion-based solutions exist that are optimal for general sources [23] and for sources with convex D-R curves [24], and it has been shown that an optimal rate-based solution is essentially an equally protected system [15]. In the case of a random bit-error channel and a source with an exponential D-R curve, efficient and optimal distortion minimization is possible [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other techniques can be found in the above references that find locally-optimal or suboptimal solutions with varying degrees of complexity. Efficient search algorithms have also been introduced that perform very close to the optimal solution [15], [22]. Error resilient techniques based on independently decodable packets and estimation of lost source symbols have also been introduced and combined with forward error correction for robust transmission of embedded bitstreams [12], [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation